Penyusunan dan Penyajian Laporan Keuangan di Lembaga Keuangan Syariah - Himyar Pasrizal; Fajrur Rahmi (Al-bank: Journal of Islamic Banking and Finance, 2021)
The purpose of this study is to provide knowledge on the preparation and position of each item contained in the transaction report on sources and uses of qardhul hasan fund and financial report on sources and zakat fund. The research method in this article is descriptive qualitative research by analyzing the two types of financial statement in islamic financial institution. The result in this study are the source and us of qardhul hasan fund in islamic financial institution sourced from infaq fund, alms, and result from the management of waqf fund and non halal income fund. Meanwile in the financial statement, the sources and uses of zakat fund come from zakat fund obtained from internal parties of islamic financial institution and external parties, namely people who are not customer of islamic financial instutions.